2014
DOI: 10.1556/eujmi-d-14-00029
|View full text |Cite
|
Sign up to set email alerts
|

Saponins increase susceptibility of vancomycin-resistant enterococci to antibiotic compounds

Abstract: The resistance of commensal bacteria to first and second line antibiotics has reached an alarming level in many parts of the world and endangers the effective treatment of infectious diseases. In this study, the influence of the plant-derived natural saponins glycyrrhizic acid, β-aescin, α-hederin, hederacoside C, and primulic acid 1 on the susceptibility of vancomycin-resistant enterococci (VRE) against antibiotics of clinical relevance was investigated in 20 clinical isolates. Furthermore, the antibacterial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
3
10
0
4
Order By: Relevance
“…The results of our experiment showed that gentamicin decreased the dose of T. terrestris, so it had a synergistic effects with gentamicin. The synergistic effects of saponins with amphotericin B, itraconazole [31], mancozeb [32], and vancomycin [33] were confirmed, while saponins had no synergistic effects with ampicillin, streptomycin and ciprofloxacin against clinical isolates [27]. The synergy between T. terrestris methanol extract and gentamicin were confirmed by two methods in this study and are reported for the first time.…”
Section: Antibacterial Activity Of Tribulus Terrestris Methanol Extrasupporting
confidence: 66%
“…The results of our experiment showed that gentamicin decreased the dose of T. terrestris, so it had a synergistic effects with gentamicin. The synergistic effects of saponins with amphotericin B, itraconazole [31], mancozeb [32], and vancomycin [33] were confirmed, while saponins had no synergistic effects with ampicillin, streptomycin and ciprofloxacin against clinical isolates [27]. The synergy between T. terrestris methanol extract and gentamicin were confirmed by two methods in this study and are reported for the first time.…”
Section: Antibacterial Activity Of Tribulus Terrestris Methanol Extrasupporting
confidence: 66%
“…On account of their antibacterial effects, saponins presumably serve the plants as defense against infection. A higher uptake of the antibiotic drugs into the bacterial cell might have been induced by the interaction of the saponins with the bacterial membrane and, hence, might have been responsible for the observed beneficial effects . Further investigation on how saponins contribute to the bacterial biofilm effect is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Saponins are also known to have antibiotic activity and many anti-tumour drug preparations used for chemotherapeutic management of various types of cancer contain saponins in their chemical formulations [21][22][23][24][25]. Even more, previous reports exist on the claims of the use of W. indica for experiential treatment of snakebites [6].…”
Section: Discussionmentioning
confidence: 99%